Postcard sent to Georg Bredig of the Katarina Elevator (1895)
Postcard of the Katarina Elevator in Stockholm, Sweden. The postcard, sent to Georg Bredig (1868-1944), is signed by well-known scientists such as Svante Arrhenius (1859-1927), Astronomer Gustav Kobb, Otto Berg (1873 -1939), and Nils Strindberg (1872-1897).
Keywords: Arrhenius, Svante, 1859-1927; Strindberg, Nils, 1872-1897; Kobb, Gustav; Bredig, Georg, 1868-1944; Chemists; Berg, Otto, 1873 -1939